The Impact of Trauma on The Self-Esteem of Black Adolescents: Moderating Effects of Boundaries in Parent- Adolescent Relationships - Chappelle, Noelle; Tadros, Eman (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: Up to 43% of youth in the United States have reported experiencing a traumatic event. This study examined the moderating effects of perceived closeness with parents upon the expected effects of experiencing trauma on the self-esteem of Black adolescents through a Structural Family Therapy lens. Methods and Materials: A hierarchical linear regression with a moderating interaction term was utilized to examine the impact of perceived closeness with parents as a moderator between experiencing trauma and self-esteem composite scores from the Young Adults Self Report of the National Longitudinal Surveys Children and Young Adults. Findings: The results indicated that perceived closeness to parents did moderate the expected results of experienced trauma upon the self-esteem of Black adolescents (R = .330 and p = .038). Conclusion: Based on these findings, marriage and family therapists are encouraged to increase their cultural competency skills and their competency with respect to trauma-informed practice when counseling Black adolescents and adolescents who may have experienced trauma. Our study found that perceived closeness to parents moderated experienced trauma on the self-esteem of Black adolescents. Based on this, marriage and family therapists are encouraged to provide culturally appropriate and trauma-informed care, especially when counseling African American adolescents and adolescents who have experienced trauma.